mGlu3 receptor and astrocytes: Partners in neuroprotection - Durand, Daniela Elizabeth (2013)
Astrocytes are currently studied intensively because of their now highlighted relevance as key players with neurons that modulate a wide range of central functions, from synaptic plasticity and synaptogenesis to regulation of metabolic and neuroinflammatory processes. Since the discovery of mGlu3 receptors on astrocytes, accumulating evidence supports a role of these receptors not only in maintaining synaptic homeostasis and treating psychiatric disorders but also in promoting astrocyte survival in several pathologic conditions. This review focuses on providing up-to-date knowledge regarding effects of activating astroglial mGlu3 receptors on psychiatric disorders, astrocyte and neuronal survival, and neurodegenerative diseases.